2007
DOI: 10.1042/bj20070382
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localization of human Ins(1,3,4,5,6)P5 2-kinase

Abstract: InsP6 is an intracellular signal with several proposed functions that is synthesized by IP5K [Ins(1,3,4,5,6)P5 2-kinase]. In the present study, we overexpressed EGFP (enhanced green fluorescent protein)-IP5K fusion proteins in NRK (normal rat kidney), COS7 and H1299 cells. The results indicate that there is spatial microheterogeneity in the intracellular localization of IP5K that could also be confirmed for the endogenous enzyme. This may facilitate changes in InsP6 levels at its sites of action. For example, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 53 publications
1
48
0
Order By: Relevance
“…12 These cytoplasmic inclusions, referred to as stress granules, are observed in cells subjected to environmental stress, including heat, irradiation, oxidative conditions, and hyperosmolarity. 13 Because we observed increased intact IPP2K in the kidney and IPP2K urinary fragments, we examined whether stress granules are present in DN.…”
Section: Changes In Ipp2k and T Cell Intracellular Antigen 1 Expressimentioning
confidence: 99%
“…12 These cytoplasmic inclusions, referred to as stress granules, are observed in cells subjected to environmental stress, including heat, irradiation, oxidative conditions, and hyperosmolarity. 13 Because we observed increased intact IPP2K in the kidney and IPP2K urinary fragments, we examined whether stress granules are present in DN.…”
Section: Changes In Ipp2k and T Cell Intracellular Antigen 1 Expressimentioning
confidence: 99%
“…In an earlier study we demonstrated that, in mammals, IP5K is predominantly a nuclear enzyme (Brehm et al, 2007). That observation has furthered general interest in understanding the significance of nuclear compartmentalization of inositol phosphate signaling (Martelli et al, 2011;Seeds et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The source of the anti-IP5K antibody (used at 1:40 dilution) was as previously described (Brehm et al, 2007). Antibody specificity was validated by the loss of signal after RNAi against IP5K (supplementary material Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations